Impacts of Cassava Mill Effluents in Nigeria - Sylvester, Chibueze Izah; Sunday, Etim Bassey; Elijah, Ige Ohimain (Journal of Plant and Animal Ecology, 2018)
Cassava is the fourth largest staple food after rice, wheat and maize. Cassava is produced in the tropical and sub-tropical countries. Currently, the global production of cassava is about 215,436,496 tons. Out of these, Nigeria accounts for 20.3%, being the largest producing nation. During processing of cassava flour (Gari), three main wastes are generated including cassava mill effluents (CME), solid and gaseous emission. This paper reviews the impacts of CME in Nigeria. The study found that CME’s physicochemical quality often exceeds the limit for effluents discharge onto land and surface water as recommended by Federal Environmental Protection Agency (FEPA), Nigeria. CME alters the quality of soil and water with regard to physicochemical, heavy metal and microbial characteristics. CME can induce toxicological effects on the environments and its biota including humans, fisheries, flora and fauna. The impacts are mostly associated with physicochemical (viz: odour, cyanide, acidic, dissolved oxygen, biological and chemical oxygen demand, conductivity) and heavy metals characteristics. Therefore, there is the need for treatment and sustainable management strategies of CME through biotechnological advancement.
Keywords: Biotechnological advances; Cassava mill effluents; Cassava; Impacts